Application of Nanotechnological Devices in Mobile Phones - Aliyev, B.H.; Gashimov, Kh.M.; Mamedova, A.E.; Sultanova, J.R. (Herald of Azerbaijan Engineering Academy, 2023)
The purpose of the work is to acquire a new type of PowerBank by applying a device obtained using nanotechnology to an existing PowerBank. For this, a Chinese-made PowerBank was purchased in China, and a new type of PowerBank (YPB) was developed by adding a solar battery made on the basis of palladium silicide using nanotechnology. YPB is powered by both battery and solar panels. On the other hand, the YPB battery can also be charged via a solar panel. The advantage of YPB is that it can work in places where there is no mains power. When charging YPB, it can be left in the network from night to morning, as the solar panel is automatically disconnected from the network after charging the battery.